Analisis Aliran Komunikasi Paska Penyederhanaan Birokrasi Studi Kasus pada Kementerian Pariwisata dan Ekonomi Kreatif/ Badan Pariwisata dan Ekonomi Kreatif (Kemenparekraf/ Baparekraf) - Pasaribu, Cindy Riona; Saksono, Eko Hari (Jurnal Mahardika Adiwidia, 2022)
This research was conducted with the background of analyzing the organization communication flow in Â the Ministry of Tourism and Creative Economy / Tourism and Creative Economy Agency (Kemenparekraf / Baparekraf) after the simplification of bureaucracy. There are three dimensions to the flow of communication, which are: downward communication, upward communication and horizonal communication. The flow of communication in bureaucratic organizations is determined by the existence of ideal bureaucratic principles according to Max Weber which include clear hierarchy, division of labor and centralization of decision-making and power. This research used quantitative methodology and using descriptive research. The population in this study amounted to 367 government employees which affected by bureaucratic simplification. Authors used Yamane formula and accidental sampling technique to get a sample of 78 peoples. The study concluded that horizontal communication occurs more in organizations, while downward communication that characterizes the ideal bureaucracy shows fewer numbers so that it requires evaluation of strengthening bureaucratic communication to strengthen the organization in the future.